THE DEVELOPMENT OF INTERCULTURAL COMMUNICATION COMPETENCE IN ENGLISH LANGUAGE LEARNING CONTEXT: CASE OF LITERATURE FOR YOUNGER AND OLDER CHILDREN COURSE - Fahira Akmalia; Adesti Komalasari (UC Journal: ELT, Linguistics and Literature Journal, 2021)
Globalization and the advancement of technology influence people to communicate with each other. Nowadays, people in different regions and countries interact with each other and intercultural interaction happens among them. In this context, there is intercultural communication when the interaction occurs. In recent years, the emergence of the Intercultural Communication Competence (ICC) concept has entered the education field. This paper discusses the integration of ICC concepts and areas to a course in one of the private universities in Jakarta and sees how the course incorporated ICC concepts for students’ ICC development. The course is Literature for Younger and Older Children that integrates the ICC concept by conducting a virtual exchange program, excursion, and a project for their students. The virtual exchange happened between the participants and their group friends from Sweden. The phenomenology qualitative method was applied to dig deep information about the participants during the course activities. Observation, participants’ video reflection and the virtual exchange program are the data of this research. The result of this research is all of the course activities support the participants to develop the ICC areas; the knowledge, skills of interpreting and relating, skill of cultural awareness, skill of interaction and discovery, and attitudes. At the end of the course, the participants have developed their intercultural communication competence.